Simulation of multiscale finite element method on graded meshes for two-dimensional singularly perturbed twin boundary layers problems - Sun, Meiling; Jiang, Shan (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2022)
To solve a two-dimensional singularly perturbed model, a multiscale finite element method on graded meshes built from the perturbed parameter is presented for capturing the twin boundary layers of convection-diffusion equations effectively. Based on the graded meshes, the multiscale basis functions are capable of subtly describing the microscopic information in the boundary layers. No wonder, it just costs a handful of computing resource and short time to achieve the accurate and efficient results, and the results are independent of the perturbed parameter with uniform stability.